PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN SELF-EFFICACY SISWA SMPN 2 BOJONGSOANG - Arsynur Fathul Fikri, - (2023)
Arsynur Fathul Fikri 185156. The Effect of Inquiry Learning Model on Students' Critical Thinking Ability and Their Self-Efficacy in SMPN 2 Bojongsoang. The selection of student learning models must be adapted to the conditions of the students, the inquiry learning model is one of the learning models that can facilitate students to exert all mathematical critical thinking ability and student self-efficacy. This study aims to determine the effect of inkuiri learning models on mathematical critical thinking ability and stundet self-efficacy. This type of research is quantitative with a quasi experiment research method. The popoulation in this study were seventh grade students of SMPN 2 Bojongsoang. The research sample consisted of two classes. The instruments used in this study were mathematical critical thinking ability test instruments and non-test instruments in the form of self-efficacy questionnaires in mathematical learning. The result of this study indicate that theres is an effect of the inquiry learning model on the achievement of mathematical critical thinking ability and self-efficacy and an increase in mathematical critical thinking ability after learning with the inquiry learning model.